Figurative Conceptualizations of Nations, Countries, and Institutions in Newspaper Articles on Migration - Mersina Mujagić (Anglica. An International Journal of English Studies, 2023)
The paper discusses figurative conceptualizations of nations, countries, and institutions as either a container, a person, a sinking ship, a fabric, or hell in media discourse on the European migrant crisis. Applying Steen et al.’s (2010) three-dimensional model of metaphor analysis, we analyze a specific set of metaphorical linguistic expressions, which are inextricably related in the segments of the real discourse on migration, to discuss their rhetorical power and communicative function. The aim of this paper is to describe and identify cases when these are used as perspective-changing devices to influence readers’ opinion on an important issue such as migration.